2015
DOI: 10.1017/s1759078715000057
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized bent slotted patch antenna over a reactive impedance surface substrate

Abstract: A reactive impedance surface (RIS) based miniaturized bent slotted patch antenna is proposed and investigated for S-band applications around 2.39 GHz. Bent slots in the patch reduce the patch antenna size by increasing current path on the patch. Further a RIS substrate with cross-shaped patch elements printed over a grounded dielectric is optimized and investigated for antenna miniaturization. The proposed bent slotted patch antenna over RIS substrate is 38.75% miniaturized with respect to traditional patch an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…On comparing Figure (a) with Figure (a), it is observed that two meander line structures are removed from the vicinity of the feedline to reduce the coupling of the RIS with the feedline which accounts for spurious radiation. From previous literature , it is observed that better miniaturization has been achieved using RIS having substrate thickness higher than that used in our work. This increases the profile of the structure and also increases its weight.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…On comparing Figure (a) with Figure (a), it is observed that two meander line structures are removed from the vicinity of the feedline to reduce the coupling of the RIS with the feedline which accounts for spurious radiation. From previous literature , it is observed that better miniaturization has been achieved using RIS having substrate thickness higher than that used in our work. This increases the profile of the structure and also increases its weight.…”
Section: Resultsmentioning
confidence: 65%
“…The simulated gain and efficiency of the proposed structure are 5.82 dBi and 79%, respectively. To highlight the significance of defected ground of the RIS, a comparison of the proposed structure with previous works is tabulated in Table . From the table, it is found that the proposed technique is able to provide maximum miniaturization by using RIS substrate of minimum thickness (for multiband structures the frequency where maximum miniaturization is obtained is referred to).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For improving the radiation efficiency an air gap was also introduced with in the structure, but structure became complex and non-planar. A number of antennas inspired by reactive impedance surface (RIS) in combination with slots, complementary split-ring resonators (CSRR), and other meta-material structure have been proposed to design smaller antennas [7–10]. In [11], a Hilbert shaped RIS and Wunderlich-shaped fractal CSRR were utilized for size reduction with low substrate thickness.…”
Section: Introductionmentioning
confidence: 99%